Fluoroquinolone-nitro imidazole fixed-dose combination medication-induced fixed drug eruption with positive re-challenge - Halder, Debjyoti; Dalal, Indrani; Das, Durbashree (International Journal of Basic & Clinical Pharmacology, 2025)
Fluoroquinolone-nitroimidazole fixed-dose combinations, such as ofloxacin-ornidazole and norfloxacin-tinidazole, are widely prescribed for gastrointestinal infections. However, fixed drug eruptions (FDEs) associated with these combinations are underreported. A 32-year-old female developed generalized itching and painful ulcerative lesions on the buccal mucosa shortly after taking an ofloxacin-ornidazole tablet. Upon discontinuation and substitution with norfloxacin-tinidazole by a physician, her symptoms worsened, indicating a positive rechallenge. Dermatological evaluation led to withdrawal of the drug and initiation of antihistamines and topical analgesics, resulting in symptom resolution. Her clinical course, including lesion recurrence at the same site upon re-exposure, confirmed the diagnosis of FDE, a delayed-type hypersensitivity reaction mediated by CD8+ T cells. Causality assessment using the World Health Organization-Uppsala Monitoring Centre (WHO-UMC) scale classified the reaction as certain. This case highlights the need for thorough drug history taking and the importance of avoiding re-prescription of drugs from the same pharmacological class in patients with suspected drug allergies.